RANCANG BANGUN APLIKASI PENERBITAN SPPD DAN SURAT IZIN CUTI BERBASIS WEB PADA KOMISI PEMILIHAN UMUM KABUPATEN MANOKWARI SELATAN : DESIGN AND DEVELOPMENT OF A WEB-BASED APPLICATION FOR ISSUING SPPD AND LEAVE PERMITS AT THE GENERAL ELECTION COMMISSION OF SOUTH MANOKWARI REGENCY - CHRISTIAN SUHENDRA; Nona Susana Pariamalinya; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2024)
Current technology has become a crucial part of an institution or company to help accelerate processes and minimize human errors. The General Election Commission (KPU) of South Manokwari Regency in West Papua Province, specifically, has not yet fully implemented leave permissions as stipulated in labor regulations for its employees, especially those bound by annual contracts. Similarly, the issuance of official travel orders (SPPD) for employees is hampered by administrative workforce issues, resulting in delays in the issuance of SPPDs as permits to leave the location for other out-of-town work. The Web-Based Application for Issuing SPPD and Leave Permits is created using the CodeIgniter framework, all of which are free licensed applications. With the design and development of this system and application, it is expected to maximize work time effectively by better controlling the leave of specialist service personnel and more efficiently managing business trips